The garden of empire - Greathouse, J. T. (Pact and pattern, 2022)
The boy once known as Wen Alder has become the rebel witch Foolish Cur. Schooled in both the powers that bound him to serve the emperor as well as the furious, wild magic of his mother's ancestors, he was torn between two worlds, until he realized the brutal nature of the emperor and his rule. Joining the rebellion, he soon experienced the painful sacrifices that come with defiance. Now the emperor - covetous of Foolish Cur's magic - has decided to take his own ruthless quest for power to the gods themselves. if he succeeds, the gods will unleash a storm of death and destruction unlike any even imagined. Only Foolish Cur has the skills and strength to stave off such a nightmare. While Foolish Cur figuts the Empire in Nayen, others wage their own rebellions. A successful tutor opens a school to preserve his own dying culture while a warrior of the plains discovers powers long thought lost. And a servant of the empire begins to question the violence that threatens to engulf them all. -- From back cover.